2021
DOI: 10.1111/apa.16019
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of children to the emergency department during the first wave of COVID‐19 pandemic in Italy: Area‐based cohort study

Abstract: Children are protected both in terms of susceptibility to SARS-CoV-2 infections and of serious illnesses. 1,2 However, the negative effect of the pandemic on children health has been widely described, from an increase of mental health problems 3 to a decreased attendance to health services. 4 A decrease in emergency department (ED) attendance has been reported in children in several countries since the early phases of the pandemic, together with a case series of delayed presentations to hospital care and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…The Diabetes Study Group of the Italian Society for Pediatric Endocrinology and Diabetology demonstrated that, during the lockdown, there were 23% fewer new diabetes cases compared to the same period in 2019 and that children presenting with DKA had more severe DKA (pH < 7.1) in 2020 than in 2019 (p = 0.03), although no diagnoses were missed overall [15]. Similar findings have been reported by other authors for other serious diseases [16].…”
Section: Discussionsupporting
confidence: 70%
“…The Diabetes Study Group of the Italian Society for Pediatric Endocrinology and Diabetology demonstrated that, during the lockdown, there were 23% fewer new diabetes cases compared to the same period in 2019 and that children presenting with DKA had more severe DKA (pH < 7.1) in 2020 than in 2019 (p = 0.03), although no diagnoses were missed overall [15]. Similar findings have been reported by other authors for other serious diseases [16].…”
Section: Discussionsupporting
confidence: 70%
“…Several studies reported reduced pediatric health care contacts, emergency department (ED) presentations, admissions, and pediatric intensive care admissions in Italy, the UK, Scotland, and Australia during local lockdowns [2,[10][11][12][13], mainly driven by substantial reductions in respiratory diseases. Trauma-specific investigations from several countries (UK, Ireland, Canada, New Zealand) showed decreases up to 60% for pediatric trauma presentations to EDs [4,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the utilization of EMS services by patients' subgroups is concerned, it is interesting to note that paediatric ED admissions and hospitalization were those most severely affected. This dramatic decline of EMS utilization in this age group is probably due to a combination of factors such as the reduction of trauma and injuries related to closure of schools, leisure and sport activities, and the reduction of recrudescence of diseases related to air pollution and of other infectious diseases [38][39][40][41]. Furthermore, it should be pointed out that inappropriate utilization of EMS is commonly reported for paediatric patients [38,42], however delayed presentation for acute illnesses-probably linked to the reduced access to primary care-were reported during the first wave of the pandemic [38,40].…”
Section: Plos Onementioning
confidence: 99%